2004
DOI: 10.1111/j.1365-2427.2004.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate limitation influences the sensitivity to copper in periphytic algae

Abstract: 1. To assess the influence of nutrient limitation on copper toxicity, periphitic communities from an oligotrophic stream were exposed to copper for six to 12 days with and without the supply of nutrients (mainly P). 2. In contrast to the hypothesis that nutrient cycling in mature biofilms would protect them from Cu toxicity, low and high biomass biofilms did not differ in their physiological response to copper after 6 days of exposure. 3. A clear influence of P-limitation on copper toxicity was observed. Perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 40 publications
4
39
0
Order By: Relevance
“…This particular study area is therefore an interesting example where environmental pressures such as urban activities may exacerbate stresses from past and present mining activities and thus affecting system recovery. This has been previously observed where a greater number of cumulative environmental stressors resulted in more significant impacts on diatom assemblages [19], although some antagonistically acting stressors have been evidenced (e.g., metals versus nutrients [20,21]). The present study provides groundwork for assessing stream biological integrity based on diatom descriptors, and brings valuable information to be used in further monitoring of the Junction Creek system recovery and health.…”
Section: Introductionmentioning
confidence: 84%
“…This particular study area is therefore an interesting example where environmental pressures such as urban activities may exacerbate stresses from past and present mining activities and thus affecting system recovery. This has been previously observed where a greater number of cumulative environmental stressors resulted in more significant impacts on diatom assemblages [19], although some antagonistically acting stressors have been evidenced (e.g., metals versus nutrients [20,21]). The present study provides groundwork for assessing stream biological integrity based on diatom descriptors, and brings valuable information to be used in further monitoring of the Junction Creek system recovery and health.…”
Section: Introductionmentioning
confidence: 84%
“…Additional multi-stress factors which might interfere with the toxicity of the herbicides are nutrient limitation (Hall et al, 1989;Guasch et al, 2004) and temperature (Chalifour and Juneau, 2011). A combination of timing as well as the presence of additional multi-stress factors will determine the herbicide toxicity in the field, while the ultimate effect on the ecosystem will also depend on the ability of the microalgae to recover from damage by solar radiation (Janknegt et al, 2009b) and/or contaminants (Buma et al, 2009;Magnusson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Guasch et al (2004) found that biofilm photosynthetic efficiency was significantly inhibited by a 6-day Cu exposure (15 µg L−1) whatever the nutrient level, whereas Tlili et al (2010) showed that the simultaneous addition of Cu and nutrients may compensate for the inhibitory effect on physiological community response. Copper may exert its toxicity by interfering with photosynthesis in the chloroplasts and ATP production (Cid et al, 1995).…”
Section: Recovery Of Phototrophic Communitiesmentioning
confidence: 96%